Dielectric relaxation and optical band-gap modulation in LuFe1-xCoxO3 powders - Carterette, R.; Coskun, M.; Sobola, D.; Yildirim, Y.; Sen, C.; Durmus, Z.; Polat, O. (Springer Heidelberg, 2026)
LuFeO3 (LFO) is a perovskite oxide with promise for optical and electroceramic applications. In the present study, LFO and Co-substituted compositions (LFO, LuFe0.95Co0.05O3, and LuFe0.90Co0.10O3) were synthesized by a conventional solid-state route and characterized by SEM, Raman spectroscopy, diffuse reflectance, and broadband dielectric/impedance measurements. Co substitution alters the powder microstructure, yielding more irregular agglomerates composed of finer sub-units than undoped LFO. Dielectric spectra showed that the loss tangent (tan delta), the dissipation factor, of investigated samples was below 1 over the studied temperature-frequency window. It was seen that Co substitution decreased dielectric loss in the mid-to-high frequency region but raised low-frequency loss at advanced temperatures. The real part of impedance Z' declined with both temperature and frequency, and Nyquist plots displayed depressed arcs, indicating non-Debye behavior with distributed grain and grain-boundary contributions. Arrhenius analysis of relaxation maxima yielded activation energies of similar to 0.32-0.76 eV, consistent with oxygen-vacancy energies. Raman spectra revealed Co-induced lattice perturbations, including mode broadening/attenuation and red-shifts in the 200-600 cm(-1) range, together with a strengthened stretching feature near 600-650 cm(-1). Kubelka-Munk analysis was utilized to determine the band gaps of the studied samples, 2.19 eV (LFO), 2.29 eV (5% Co), and 2.14 eV (10% Co). Overall, modest Co substitution provides an effective route to tailor vacancy-mediated relaxation and reduce MHz-range dielectric dissipation in LFO-based functional ceramics.
Keywords: LuFeO3; Solid-state reaction; Co substitution; Raman spectrum; Loss tangent (tan); Optical band gap